Multi-institutional 1-Year Bulbar Urethroplasty Outcomes Using a Standardized Prospective Cystoscopic Follow-up Protocol - Erickson, Bradley A. (Urology, 2014)
OBJECTIVE: To evaluate multi-institutional outcomes of bulbar urethroplasty utilizing a standardized cystoscopic follow-up protocol. METHODS: Eight reconstructive surgeons prospectively enrolled urethral stricture patients in a multi-institutional study and performed postoperative cystoscopy at 3 and 12 months. Anatomic failure was defined as the inability to pass a flexible cystoscope without force. Functional failure was defined as the need for a secondary procedure. Men not compliant with the 12-month cystoscopy were called and asked if any interval secondary procedures had been performed. Patients with bothersome voiding complaints at cystoscopy were considered symptomatic. RESULTS: Of 213 men in study, 136 underwent excisional urethroplasty (excision and primary anastomosis [EPA]) and 77 underwent repair with buccal grafts. Cystoscopy compliance was 79.8% at 3 months and 54.4% at 12 months. Anatomic success rates were higher at 3 vs 12 months for EPA repairs (97.2% [106 of 109] vs 85.5% [65 of 76; P = .003] but not buccal repairs (85.5% [53 of 62] vs 77.5% [31 of 40]; P = .30). Functional success rates at a year were higher but statistically similar to anatomical success rates (EPA—90.3% [93 of 103]; P = .33; buccal—87% [47 of 54]; P = .22). Of the 20 anatomic recurrences, only 13 (65%) were symptomatic at the time of cystoscopic diagnosis. CONCLUSION: Rates of success are lower when using the anatomic vs traditional definition. Of recurrences found by cystoscopy, only 65% were symptomatic. One-year patient cystoscopy compliance was poor and its ability to be used as the gold standard screening methodology for recurrence is questionable.